USE OF WORD FORMATION MODELS IN DYSARTHRIC CHILDREN (American Journal of Pedagogical and Educational Research, 2023)
The famous linguist A.N. Gvozdev collected unique factual materials in his research "The formation of the child's vocabulary is closely related to the word formation processes, because as word formation develops, the child's vocabulary is rapidly enriched at the expense of derivative words. The lexical level of the language is a set of lexical units that are the result of word formation actions and mechanisms.